2019
DOI: 10.3390/biom9110720
|View full text |Cite
|
Sign up to set email alerts
|

Is Sotolon Relevant to the Aroma of Madeira Wine Blends?

Abstract: Madeira wine (MW) oxidative aging results in the formation of several key aromas. Little is still known about their odor relevance to the aroma of the most commercialized MWs. This report presents an in-depth study of the odor impact of sotolon in MW blends. First, its odor perception was estimated in MWs according to ASTM E679, testing different 3-year-old (3-yo) commercial blends. The odor relevance of sotolon in the aroma of 3-, 5-, and 10-yo commercial blends (89 MWs) was then appraised by calculating its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Previously, an odour detection threshold of 23 µg/L was reported for sotolon in MWs [19]. Considering this, one can observe that sotolon significantly contributes to the aroma of sweet estufagem aged wines, reaching OAVs of up to 17.5.…”
Section: Sotolon Quantificationmentioning
confidence: 76%
See 2 more Smart Citations
“…Previously, an odour detection threshold of 23 µg/L was reported for sotolon in MWs [19]. Considering this, one can observe that sotolon significantly contributes to the aroma of sweet estufagem aged wines, reaching OAVs of up to 17.5.…”
Section: Sotolon Quantificationmentioning
confidence: 76%
“…In the corresponding wines aged under the canteiro ageing system, its odorant impact was less expressive, and OAVs were lower than 2.9. Moreover, the average OAVs of 3-, 5-, and 10-year-old MWs were found to be 2.8, 6.3, and 9.8, respectively [19]. Thus, the soloton odorant impact in the sweet wines aged by the estufagem process surpassed the average value obtained for 10-year-old MWs while those aged by canteiro were comparable to 3-year-old MWs.…”
Section: Sotolon Quantificationmentioning
confidence: 77%
See 1 more Smart Citation
“…Perestrelo et al [80] observed that pantolactone, γ-ethoxybutyrolactone, γ-heptalactone, trans-oak-lactone, and cis-oak-lactone are highest and positively correlated with age for Madeira wines obtained from Malvasia and Boal. In addition, sotolon (3-hydroxy-4,5-dimethyl-2(5H)-furanone) has been considered a key aroma of fortified wines owing to its low OT (few µg/L) and, associated with their characteristic nutty, caramel, and curry odor, depends on its concentration and enantiomeric distribution [95]. According to Câmara et al [89], the concentration of sotolon increases significantly during ageing from 100 (6 year-old) to 1000 µg/L (25-year-old), and for this reason, can be considered a potential ageing marker and a strong contributor to Madeira wine with spicy aromas.…”
Section: Lactonesmentioning
confidence: 99%
“…Additionally, grape-derived wine aroma molecules accumulate in quite different time periods of winemaking; some of them are mostly released during fermentation, while some others accumulate only after long periods of aging. Gaspar et al [13] also studied the odor relevance of sotolon aroma in Madeira wine blends. The results showed that sotolon has an important contribution to the aroma of commercially available Madeira wine blends, particularly in those with long aging periods.…”
mentioning
confidence: 99%